2019
DOI: 10.1038/s41598-018-36611-w
|View full text |Cite
|
Sign up to set email alerts
|

INITIAL – An observational study of disease severity in newly diagnosed asthma patients and initial response following 12 weeks’ treatment

Abstract: In China, there are an estimated 30 million people with asthma, a condition that remains poorly controlled in many patients. The INITIAL study (NCT02143739) was a 12-week, multicentre, prospective, observational study comprising 45 centres across Northern and Southern China that aimed to assess asthma severity among newly diagnosed patients as well as their prescribed medications and response to treatment. The primary objective was to evaluate asthma severity using Global Initiative for Asthma (GINA) 2006 rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The addition of a third controller (LTRA or theophylline) is an option for patients who are not adequately controlled with a medium-dose ICS/LABA after a trial of 2-3 months for patients at Step 4 [1,2]. Among ICS/LABA medications, budesonide/formoterol is recommended by GINA 2019 as the preferred formulation of ICS-formoterol at step 1 and 2 based on the evidence of efficacy, and it was also the predominant form used in our population at baseline (88.9%, 3602/4051) [13], probably because of their availability in one inhaler (e.g. Symbicort) and easy inhaler techniques.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of a third controller (LTRA or theophylline) is an option for patients who are not adequately controlled with a medium-dose ICS/LABA after a trial of 2-3 months for patients at Step 4 [1,2]. Among ICS/LABA medications, budesonide/formoterol is recommended by GINA 2019 as the preferred formulation of ICS-formoterol at step 1 and 2 based on the evidence of efficacy, and it was also the predominant form used in our population at baseline (88.9%, 3602/4051) [13], probably because of their availability in one inhaler (e.g. Symbicort) and easy inhaler techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This was a post hoc analysis of a 12-week, multicentre, prospective, observational study performed in patients with asthma from 45 centres across Northern and Southern China between June 2014 and September 2016 (INITIAL, NCT02143739). The protocol, full details of the study population and overall results have previously been reported [13]. Methods specific to this post hoc analysis are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations